Constitutionality of the Separation of National and Regional Elections: A Legal Review of Constitutional Court Decision No. 135/PUU-XXII/2024 on Article 22E of the 1945 Constitution - Muhamad Farid Supele (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article examines the constitutionality of separating national and local elections through a juridical analysis of Constitutional Court Decision 135/PUU-XXII/2024 in relation to Article 22E of the 1945 Constitution. The separation of elections has become a significant constitutional issue, particularly concerning the interpretation of electoral simultaneity mandated by the constitution. Using normative juridical methods, this research analyzes the Constitutional Court's reasoning and its implications for Indonesia's electoral system. The findings indicate that while the separation may offer practical benefits, it raises constitutional questions regarding the implementation of Article 22E UUD 1945.